Question about Apple Mac Book Pro 15.4" 2.53 Core2Duo 4GB RAM 320GB 5400 RPM HDD SuperDrive Mac Notebook

Ad

The answer is simple algebra. This post should be on a math site.

Posted on Oct 24, 2012

Ad

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

Best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of.(from cars to computers, handyman, and even drones)

click here to download the app (for users in the US for now) and get all the help you need.

Goodluck!

Posted on Jan 02, 2017

Ad

x equals 1

First multiply the numbers outside the parentheses by what is inside the parentheses, which results in:

6 - 2x + 3x - 3 = 4x

then combine what you can:

6 - 3 = 3,

-2x + 3x = 1x

which leaves:

3 + x = 4x

Subtract the x on the left from the 4x on the right and you get:

3 = 3x

Divide by 3 to get the x alone

3 / 3 = 1

x = 1

First multiply the numbers outside the parentheses by what is inside the parentheses, which results in:

6 - 2x + 3x - 3 = 4x

then combine what you can:

6 - 3 = 3,

-2x + 3x = 1x

which leaves:

3 + x = 4x

Subtract the x on the left from the 4x on the right and you get:

3 = 3x

Divide by 3 to get the x alone

3 / 3 = 1

x = 1

Feb 02, 2014 | SoftMath Algebrator - Algebra Homework...

if you mean {7(2)2+[(3-2)-4x(3)]2} or 7(2)2+[(3-2)-4x(3)]2

{28+[(1)-12]2}

{28+[-12]2}

{28+-24}

=4

or if it was 4x not 4 times

{7(2)2+[(3-2)-4x(3)]2}

28+[(1)-12x]2

28+-24x

=-28x+28

{28+[(1)-12]2}

{28+[-12]2}

{28+-24}

=4

or if it was 4x not 4 times

{7(2)2+[(3-2)-4x(3)]2}

28+[(1)-12x]2

28+-24x

=-28x+28

Jun 12, 2013 | Office Equipment & Supplies

The easiest solution would be to move the variable to only one side. This is not that difficult. For example your given equation is 8(3x-5)-4=4x-10; subtracting both sides of this equation by 4x would give 8(3x-5)-4-4x=10.

Jun 28, 2010 | Texas Instruments TI-82 Calculator

4x+7=11 Solve for "x".

subtract 7 from each side of the equation

4x +7(-7)=11(-7) = 4x=4

divide both sides of the equation by 4

4x/4=4/4

therefore

x=1

Correct?

subtract 7 from each side of the equation

4x +7(-7)=11(-7) = 4x=4

divide both sides of the equation by 4

4x/4=4/4

therefore

x=1

Correct?

Dec 06, 2009 | 2006 Harley Davidson FXDI35 35th...

Hi,

This calculator does not have a Solve function or a solver. However this example of yours is very simple that you can do it by hand. If you do not mind I will show you how to solve it. Not everything needs a calculator.

You want to solve for x. OK

This calculator does not have a Solve function or a solver. However this example of yours is very simple that you can do it by hand. If you do not mind I will show you how to solve it. Not everything needs a calculator.

You want to solve for x. OK

- Start by gathering similar terms 4x-x =3x; -13+5 =-8
- Rewrite your equation as 3x+1=2x-8
- Make the +1 change side while changing its sign
- 4x+1 -1 = 2x-8 -1 or 4x=2x-9
- Make +2x on the Right hand side go to the left hand side, changing its sign in the process 4x-2x=-9 or 2x=-9
- Divide both members by 2. This gives
- x=-9/2 or -4.5 if a decimal result is required.

Dec 06, 2009 | Texas Instruments TI-30XA Calculator

Hello,

I am not lecturing you but I would rather you understand how to do the manipulations involved in isolating a variable.

You want to isolate y, Ok

Start stripping it of all that is not y.

3y + 4x =6. (Addition is commutative, I can change the order of addition)

The term with y is** added **to 4x. If I want the term in y alone on one side I perform the** inverse operation of addition**, a **substraction**. I subtract 4x from both sides.

3y+4x-4x=6-4x. But 4x-4x=0, and we are left with

**3y= - 4x+6**

This operation is sometimes summarized as make one term change side while changing its sign

It would do no harm to put the right side of the foregoing equation in parentheses. I do that to avoid errors)

3y= (-4x+6).

Now y is**multiplied** by the number 3. To isolate y I have to perform the **inverse operation** of the multiplication, namely the division by 3

3y/3 =(-4x+6)/3. The left hand side is just y

**y= (-4x+6)/3.**

While result is correct, I can also open the parentheses

y= -4x/3 +6/3

**y= -(4/3)*x +2.**

Hope it helps.

I am not lecturing you but I would rather you understand how to do the manipulations involved in isolating a variable.

You want to isolate y, Ok

Start stripping it of all that is not y.

3y + 4x =6. (Addition is commutative, I can change the order of addition)

The term with y is

3y+4x-4x=6-4x. But 4x-4x=0, and we are left with

This operation is sometimes summarized as make one term change side while changing its sign

It would do no harm to put the right side of the foregoing equation in parentheses. I do that to avoid errors)

3y= (-4x+6).

Now y is

3y/3 =(-4x+6)/3. The left hand side is just y

While result is correct, I can also open the parentheses

y= -4x/3 +6/3

Hope it helps.

Oct 22, 2009 | Texas Instruments TI-89 Calculator

(4+x)(5-x)=(2+x)(7-x)

20-4x+5x-x^2=14-2x+7x-x^2

20+x=14+5x

20-14=4x

x=3/2:ans;

20-4x+5x-x^2=14-2x+7x-x^2

20+x=14+5x

20-14=4x

x=3/2:ans;

Oct 21, 2009 | SoftMath Algebrator - Algebra Homework...

6x+6=4x+12

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Sep 10, 2009 | Audio Players & Recorders

4x+8y=20 || /4

x+2y=5

x=5-2y

-4x+2y=-30 || /2

-2x+y=-15

-2(5-2y)+y=-15

-10+4y+y=-15

5y=-5

y=-1

x=5-2y || y=-1

x=5-2(-1)

x=5+2

x=7

x+2y=5

x=5-2y

-4x+2y=-30 || /2

-2x+y=-15

-2(5-2y)+y=-15

-10+4y+y=-15

5y=-5

y=-1

x=5-2y || y=-1

x=5-2(-1)

x=5+2

x=7

Mar 10, 2009 | Bagatrix Algebra Solved! 2005 (105101) for...

Just plug in one side of the equation and find the answer. Then plug in the other side and compare answers.

Feb 19, 2008 | Texas Instruments TI-89 Calculator

Sep 29, 2017 | Apple Mac Book Pro 15.4" 2.53 Core2Duo 4GB...

39 people viewed this question

Usually answered in minutes!

×